Trends in primary multidrug-resistant tuberculosis in the State of Rio de Janeiro: a retrospective study conducted during 2000-2019 - Bhering, Marcela; Kritski, Afrânio (Revista da Sociedade Brasileira de Medicina Tropical, 2021)
We analyzed the trends in primary multidrug-resistant tuberculosis (MDR-TB). We performed a time series analysis of primary MDR-TB cases reported in the State of Rio de Janeiro (RJ) during 2000-2019. The annual percent change and the average annual percentage change (AAPC) were computed using joinpoint regression analysis. The percentage of cases increased from 7.69% in 2000 to 38.42% in 2018. We observed an upward trend during this period (AAPC = 9.4; 95% confidence interval 1.4-18.0, p < 0.001). The trend indicates the increasing occurrence of MDR-TB transmission sources in RJ during 2000-2019.